Sistemas de manejo e população de plantas na cultura do feijoeiro comum - Martins, Fábio Aurélio Dias (2016)
This study aimed to: to evaluate the technical and economic effects of the adoption of integrated production, compared to the application previously staggered of form inputs at different levels, and to evaluate the behavior of nine different growing carioca bean of under different sowing densities. To achieve the proposed objectives were conducted 20 field trials in five different locations in the state of Minas Gerais. Three experiments comparing different production systems including integrated production, being that two of them there was the comparison to the integrated production using seed inoculated with bacteria that promote FBN. Were also conducted 17 experiments, eight in Madre de Deus de Minas each with a cultivar subjected to six planting densities with eight repetitions in a randomized block design. And nine experiments in Lambari, also each with a cultivar, but subjected to five plant populations, with six repetitions in a randomized block. The experiments of each locality were analyzed together allowing you to compare cultivation. We evaluated whenever possible grain yield, and primary income components. For PI testing economic analysis was performed through the costs for tests with variable nitrogen fertilization were evaluated foliar N concentration and grain and accumulation in the grains. Readings were taken SPAD (indirect readings of chlorophyll) and where possible obtained the ISN. In cultivation comparison tests on different plant population evaluated the effect on weed plants in the experiments. Finally it was concluded that: PI provides similar or even higher to treatments where much higher doses of inputs are applied with greater economic sustainability of bean IP, even in conditions where the achieved productivity does not allow the payment of all cost, and allows an activity with greater economic viability. Higher plant populations provided higher grain yield in experiments conducted in Lambari. •Corda de Viola and Poaia rope had reduced frequency with increasing plants population. The cultivation BRSMG Madrepérola and BRS Notável stood out with the highest yields in both growing environments.